How Small Should an Economy's Fiscal Deficit Be? : A Monetary Programming Approach - Beckerman, Paul Ely ca. Ende 20. Jh./Anfang 21. Jh (The World Bank, 1999)
March 2000 - A spreadsheet planning model to help determine the government deficit consistent with a specified vector of country macroeconomic objectives. Beckerman describes a spreadsheet planning model to help determine the government deficit consistent with a policymaker's vector of principal macroeconomic objectives (including real GDP growth, inflation, exchange rate, and international reserve accumulation). The model focuses on the monetary accounts, applying balance-of-payments forecasts formulated separately but based on the same macroeconomic objectives. The model is a consistency exercise, intended as part of a broader consistency exercise for a given macroeconomy. It offers one more perspective on the question of how large a government deficit should be - a perspective that can be used in conjunction with others. For each forecast period, the model determines consistent period-end and period-average stocks for the economy's outstanding central bank assets and liabilities and government obligations. It applies forecasting assumptions about interest rates to forecast central bank profit-and-loss flows, and takes account of these in determining the overall flow of resources that would be available to finance the government deficit. An annex describes a (purely illustrative) simulation carried out during 1999 for Ecuador. This paper - a product of the Poverty Reduction and Economic Management Sector Unit, Latin America and the Caribbean Region - is part of a larger effort in the region to strengthen the tools for macroeconomic policy analysis and planning in the region's economies. The author may be contacted at pbeckerman@worldbank.org